PENINGKATAN MEDIA EDUKASI HIBURAN MELALUI TEKNOLOGI AUGMENTED REALITY DI MUSEUM NASIONAL INDONESIA - Atmadi, Gayatri; Sepang, Nurul Robbi (Universitas Muhammadiyah Magelang, 2026)
Augmented reality is the latest information and communication technology that combines the real world with the virtual world in the form of audio visuals. Augmented reality technology can be used to meet various needs, including for tourism communication media in Jakarta. The National Museum of Indonesia is one of the educational and entertainment tourism destinations located in the center of Jakarta. The purpose of this study was to obtain a descriptive analysis of the video display in the imersif room - National Museum of Indonesia. The basis of thought used is augmented reality technology, edutainment, tourism communication media and social construction of reality. The research method uses a qualitative research type with data collection techniques carried out through surveys, interviews, analysis of message content in videos and digital references. The results of the study show that technological innovation in the imersif room can make visitors explore Indonesian history in an interactive format to re-imagine the narrative of Indonesian history. The conclusion of the study shows that the use of videos that utilize augmented reality technology is a tourism communication media that can attract the attention of domestic and foreign tourists for historical journeys in Indonesia.